Self-esteem and appearance anxiety among Chinese college students: the roles of social media use and upward social comparison - Shang, Anqi; Bao, Han (Frontiers in Psychology, 2025)
This study aimed to examine the mechanisms underlying the association between self-esteem and appearance anxiety, and whether these mechanisms differ by gender. Using structural equation modeling (SEM), we investigated interrelationships among self-esteem, social media use, upward social comparison, and appearance anxiety in a sample of 487 college students (52% female) from Jilin and Shanxi provinces, China. Our analysis showed a significant negative correlation between self-esteem and appearance anxiety. This association was partially explained by social media use and a tendency to make upward social comparisons, and this indirect effect was found to be moderated by gender. Specifically, among males, making upward social comparisons was not associated with appearance anxiety. Our findings provide insights into the link between low self-esteem and appearance anxiety in an understudied population.